Association between Elevated Serum Tau Protein Level and Sepsis-Associated Encephalopathy in Patients with Severe Sepsis. (17th July 2019) - Zhao, Teng; Xia, Yan; Wang, Dawei; Pang, Li
Abstract : Sepsis-associated encephalopathy (SAE) is a common complication of sepsis. It is imperative to recognize, diagnose, and effectively manage SAE at the early stages. The aim of this study was to evaluate the potential of using the serum tau protein level in the diagnosis of SAE and the prediction of SAE outcomes. This was a retrospective and observational study. The patients included in this study were diagnosed with severe sepsis or septic shock. The serum tau protein level was measured using a commercial enzyme-linked immunosorbent assay. The association between the level of serum tau protein and SAE was assessed by multiple logistic regression analysis. One hundred nine patients with severe sepsis were enrolled during a period of two years. Of the 109 enrolled patients, 27 developed SAE. The serum tau protein level was significantly higher in the patients with SAE than that of the non-SAE group. The serum tau protein level and the sequential organ failure assessment (SOFA) score were independent factors that were associated with SAE. The combined use of the serum tau protein level with the SOFA score improved the accuracy in distinguishing SAE from non-SAE patients. A cutoff value serum tau protein level of 75.92 pg/mL had 81.1% sensitivity and 86.1% specificity in predicting the 28-day mortality in patients with severe sepsis. We identified a close association between the serum tau protein level with the appearance of SAE in patients with severe sepsis. The serum tau protein level can be useful in the prediction of poor outcomes in patients with sepsis.